.Preconditions of the concept of helth forming technologies in the process of physical education of primary school-aged children. - N.M. Goncharova (H.S. Skovoroda Kharkiv National Pedagogical University, 2018)
On the basis of the data from scientific and methodological resources as well as systematic approach, the most challenging issues of contemporary development of physical education system in general secondary education establishments are reviewed, unsolved issues concerning implementation of health forming technologies into the process of children's physical education are considered. The aim of the research is to examine preconditions of developing the concept of health forming technologies in the process of physical education of primary-school aged children. Research methods. The complex of research methods, including analysis and generalization of the data from scientific and methodological resources, normative and regulatory documents, Internet sources in order to gain scientific information regarding terminology of health formation; systematic approach and forecasting in order to analyze changing phenomena as well as defining promising directions is used. Results. The basic causes of the necessity to introduce health forming technologies in the process of physical education of primary-school aged children are determined. Social, biological and personal preconditions of the activity regarding formation of school-aged children health are defined. Social preconditions include society's need for harmoniously developed personality, low level of formation of healthy lifestyle principles, revealing social request for population health. The group of biological preconditions contains a low level of children's motor activity, a high level of their morbidity, display of violations in children's adaptation to school conditions, the change of the children's static dynamics in connection with the beginning of systematic schooling. Personal preconditions reveal absence of a children's careful attitude towards their own health and of their need for systematic health forming activity. Conclusions. The defined preconditions and their characteristics are the tool of developing and implementing the concept of health forming technologies in the process of physical education of primary-school aged children.